Inflammation of Actinic Keratoses Induced by Combination of Carboplatin and Paclitaxel: Two Case Reports - Špela Šuler Baglama; Anja Trajber Horvat; Irena Peteln; Gregor Borut Ernst Jemec (Karger Publishers, 2022)
The observations of a beneficial effect of 5-fluorouracil-induced actinic keratoses (AK) inflammation led to the development of topical fluorouracil, a product registered for the management of AK. A conscientious surveillance of AK inflammation during chemotherapy may conceivably lead to the development of further drugs for treatment of AK. A number of other chemotherapeutics have thus been linked to similar reactions without ensuing development. Here, we describe two further cases linking chemotherapy with carboplatin and paclitaxel to possible anti-AK effects, identifying them as potential treatments. Whether multidrug chemotherapy leads to stronger AK inflammation or cure AK more successfully is currently unknown.